INFLUENCE OF GROUP COUNSELING SERVICES SELF MANAGEMENT TECHNIQUES ON THE DISCIPLINE OF STUDENTS IN JUNIOR HIGH SCHOOL - Ellis, Rusnawatii; Holimombo, Choirun A; Wenno, Yulian Hermanus (Journal of Health and Behavioral Science, 2024)
Abstract The phenomenon in the field is that there are various indisciplines of students who like to ignore their studies at school and homework. Discipline is an element of a person's morality that emphasizes rules and regulations in the principles of order, giving orders, prohibitions, praise, and punishment with authority or coercion to achieve good conditions. Students who lack discipline can be overcome by providing group counseling services with self-management techniques. This research aims to determine the effect of self-management technical group counseling services on student discipline at Junior high school. The approach to this research uses quantitative research methods with a one- group pre-test and post-test design with a research sample of 10 respondents who are class VIII students at Junior high school. Based on the results of this study, it shows that the pre-test before being given treatment was 60.00% while the increase after being given treatment was 80.20%. So between the pre-test and post-test, the average value (Mean) is 20.200%. The Paired Sample t-test test has a significant value of 0.000, which means 0.00 <0.05. So it can be concluded that Ho is rejected and Ha. accepted.